1994
DOI: 10.1288/00005537-199411000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Four‐year follow‐up after uvulopalatopharyngoplasty in 50 unselected patients with obstructive sleep apnea syndrome

Abstract: Fifty unselected consecutive patients with obstructive sleep apnea syndrome (OSAS) diagnosed by nocturnal recordings of respiration movements by a static charge sensitive bed (SCSB) and oximetry, alone or combined with polysomnography, were studied. Renewed SCSB-oximetry recordings evaluated treatment. Six months after surgery, 30 of 50 were classified as responders. Twenty-one months after surgery, 19 of 49 were responders. Patients who relapsed showed a significant increase in mean body mass index (BMI). Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 18 publications
3
82
1
4
Order By: Relevance
“…In the control PSG, performed in 84% of these patients, a significant reduction in sleep-disordered breathing and cure of SAHS was observed in 35%, which could have had a similar influence to that of treatment with nCPAP. It should be emphasised that patients who received both treatments maintained a weight lower than that at diagnosis, which has been proved to be an important factor in maintaining the benefits achieved with them [27,28] and which has been related to the periodic clinical follow-up [28]. Furthermore, the periodic clinical follow-up of these patients permitted the detection of therapeutic failures and establishment of alternative treatment that may have favoured the results of treatment with diet or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the control PSG, performed in 84% of these patients, a significant reduction in sleep-disordered breathing and cure of SAHS was observed in 35%, which could have had a similar influence to that of treatment with nCPAP. It should be emphasised that patients who received both treatments maintained a weight lower than that at diagnosis, which has been proved to be an important factor in maintaining the benefits achieved with them [27,28] and which has been related to the periodic clinical follow-up [28]. Furthermore, the periodic clinical follow-up of these patients permitted the detection of therapeutic failures and establishment of alternative treatment that may have favoured the results of treatment with diet or surgery.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The patients in the present study have previously been evaluated at 6 months, 2 and 4 years postoperatively regarding excessive daytime sleepiness (EDS) and renewed sleep apnoea recordings. (4) , (5) They showed significant decreases in the mean oxygen desaturation index of 4% (ODI 4 ), but 50% of the patients were regarded as failures (ODI 4 > 20 with reduction < 50%). Another long-term study on 34 patients by Janson et al, (6) using stricter success criteria (AHI < 10 with reduction > 50%), found that 52% were failures 4-8 years after UPPP surgery.…”
Section: Introductionmentioning
confidence: 99%
“…We hoped that this would allow for a more uniform interval between surgery and PSG assessment. We realize a limited time window prevents detection of delayed complications that might jeopardize UPPP response over time, 28,29 such as cicatricial narrowing at the velopharyngeal-oropharyngeal junction and potential alterations in pharyngeal sensitivity, 30,31 because the effectiveness of UPPP has been shown to decrease in the long term. 32 …”
Section: Discussionmentioning
confidence: 99%